Successfully treated but not fit for purpose: paying attention to chronic lung impairment after TB treatment - Harries,AD; Ade,S; Burney,PGJ; Hoa,NB; Schluger,NW; Castro,JL (International Journal of Tuberculosis and Lung Disease, 2016)
In 2013, 86% of patients with newly diagnosed tuberculosis (TB) successfully completed treatment and were discharged from care. However, long-term studies in industrialised and resource-poor countries all point to a higher risk of death in TB survivors than in the general population. The likely explanation is chronic restrictive and obstructive lung disease consequent to TB. We call for better linkages between TB control programmes and respiratory medicine services, a better understanding of the burden of respiratory disability at the end of antituberculosis treatment, and political, programmatic, clinical and research action to improve the quality of life of affected patients.